Hubungan Kepemimpinan Kepala Sekolah Dan Motivasi Berprestasi Terhadap Kinerja Guru Sekolah Dasar - Yulianti, Yulianti; Patras, Yuyun Elizabeth; Fatmasari, Rhini (JURNAL MANAJEMEN PENDIDIKAN, 2023)
THE RELATIONSHIP BETWEEN PRINCIPAL LEADERSHIP AND ACHIEVEMENT MOTIVATION ON ELEMENTARY SCHOOL TEACHER PERFORMANCEThis study aims to: 1) Determine the relationship between the leadership of the school principal and the performance of teachers in Tapos District, Depok City. 2) Knowing the relationship between achievement motivation and teacher performance in Tapos District, Depok City. 3) Knowing the relationship between the principal's leadership and achievement motivation together on teacher performance in Tapos District, Depok City. This research is a quantitative research type of correlation with the survey method. The data in this study were taken using a questionnaire. considering matters in sampling, the researchers took a sample that was used as a respondent by 20% of the total population, totaling 648 people. So the sample results with a total of 129.6 are rounded up to 130 people. The analysis technique used in testing the hypothesis is a simple linear regression analysis technique and multiple linear regression analysis techniques. The results of the study show that: 1) There is a significant influence between the Principal's leadership on teacher performance, indicated by a significant value probability or 0.001 0.05; 2) There is a significant influence between achievement motivation on teacher performance, indicated by a significant value probability or 0.000 0.05; 3) There is a significant influence between the Principal's leadership and achievement motivation simultaneously (together) on teacher performance, indicated by a significant value probability or 0.000 0.05. The simultaneous effect is 55.2% and the remaining 44.8% is influenced by other variables outside the regression equation or other variables not examined.